A study to find the utility of MRI in the evaluation of painful hip joints - Dr. Vinay NVP; Dr. K Jaya Sudha; Dr. Meka Lakshmi Vineela; Dr. T. Jaya Chandra (International Journal of Medical Research and Review, 2020)
Introduction: Magnetic resonance (MR) imaging is a valuable tool in the evaluation of hip disorders. With these, a study was conducted to assess the role of MRI in the early evaluation of painful hip joints. Materials and Methods: It was a cross-sectional study conducted in the department of Radiodiagnosis, GSL Medical College, Rajahmundry. The study protocol was approved by the Institutional Ethical Committee. Patients presenting with acute or chronic hip pain pathology of all age groups, both gender who referred for MRI were included in the study. Imaging has been done with 1.5 Tesla Philips Achieva machines using abdominal surface coils and spine coils. Results: Out of the 30 participants, avascular necrosis was diagnosed in 46.6% (14) participants, joint effusion in 10% (3) cases, osteoarthritis (OA) in 4 (13.3%) cases, tuberculosis (TB) in 10% (3), 6.6% (2) each was diagnosed to be Perthe’s, developmental dysplasia of the hip (DDH) and metastasis, respectively. All the pathological findings were diagnosed using MRI also. Conclusion: MRI helps in the evaluation of the involvement of articular cartilage in the form of T2W hyperintensity. It also helps in the evaluation of soft tissue involvement along with the detection of bone marrow edema.